First record of the genus Coeleumenes van der Vecht from the Philippine Islands, with description of a new species (Hymenoptera: Vespidae: Eumeninae) - Selis, Marco (Zootaxa, 2024)
The genus Coeleumenes van der Vecht, 1963 is recorded from the Philippine Islands for the first time, with Coeleumenes rusticanus sp. nov. from Mindanao. A key to the species occurring in the Malay Archipelago is provided, and Coeleumenes flavus Nguyen, 2016 and C. chumomray Mai & Nguyen, 2021 are synonymized under C. impavidus (Bingham, 1897) syn. nov.